Estudo da substituição da areia natural por pó de pedra na produção de concreto convencional - Silva, Valdeir Tavares da (Universidade Federal Rural do Semi-Árido, 2018)
Currently, construction is the sector responsible for a considerable consumption of diverse natural resources. And the natural sand is an example of these nonrenewable resources, and in Brazil, its extraction takes place from the beds of the rivers, causing a series of environmental problems. Given this scenario and the growing concern with environmental protection, it is necessary to seek alternatives that provide partial or total substitutes for these natural resources, thus minimizing the impacts caused by their extraction. Considering these issues, we propose a study on the production of Portland cement concrete with the total replacement of natural sand by artificial sand (stone dust) from the crushing process, with no final destination in construction, remaining stored in the patios of the quarries, forming huge hills, causing several environmental impacts. The present research analyzed the total replacement of natural sand by stone powder in the production of conventional concrete. To carry out this work granulometric characterization tests were conducted on materials, natural sand, stone powder and modified stone powder that comprised the study concrete, analyzing their behavior in the frustum of the abatement tests (Slump Test), from of a pre-established water / cement ratio. After this phase, cylindrical specimens of concrete were made, using 3 different traces, one reference composed of natural sand (AN), one with artificial sand of stone powder (APP) and the other with artificial sand of powder of modified stone (APPM), for an axial compression strength of 20 MPa at 28 days. The specimens were cured and subjected to the compressive strength test. The results show a greater amount of fine stone powder and in the presence of very thick material in its particle size distribution, especially in the sieve 1,18mm, where necessary the composition of a new stone powder (PPM) wherein a particle size curve within the usable limits established by standard NBR 7211 (2009). As for the axial compressive strength, all concrete produced values were very close, with their resistance being lower than expected (20 MPa). In view of these results it is feasible to replace natural sand with stone powder, but without structural purposes.
Monografia
Keywords: Construção civil; Resíduo; Britagem; Civil construction; Waste; Crushing; ENGENHARIAS::ENGENHARIA CIVIL